2003
DOI: 10.1177/0047287503257488
|View full text |Cite
|
Sign up to set email alerts
|

Urban Residents’ Attitudes toward Tourism Development: The Case of Crete

Abstract: This paper focuses on the identification and explanation of the attitudes of a sample of urban residents towards tourism development on Crete and their grouping with respect to these attitudes. Urban residents of Crete are quite strong in their support for tourism. However, the residents are not homogenous in their perceptions of tourism development. Education and employment in tourism were found to be the major single factors affecting the attitudes of residents of the island. A segmentation procedure based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
324
2
31

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(428 citation statements)
references
References 83 publications
17
324
2
31
Order By: Relevance
“…In his studies, respondents chose the following list of works and facilities: provision of recreation facilities; forest roads; reforestation; watering-troughs; information centers and landscape architecture works. Some authors [41][42][43][44] have concluded that inhabitants of heavily tourism-developed regions have better knowledge of the negative impacts of recreational use, but at the same time they prefer further development of tourism infrastructure. Similarly, our findings show that respondents are aware of the environmental problems caused by massive tourism development, but at the same time, they support the opening of a new border crossing in the central part of the NP.…”
Section: Discussionmentioning
confidence: 99%
“…In his studies, respondents chose the following list of works and facilities: provision of recreation facilities; forest roads; reforestation; watering-troughs; information centers and landscape architecture works. Some authors [41][42][43][44] have concluded that inhabitants of heavily tourism-developed regions have better knowledge of the negative impacts of recreational use, but at the same time they prefer further development of tourism infrastructure. Similarly, our findings show that respondents are aware of the environmental problems caused by massive tourism development, but at the same time, they support the opening of a new border crossing in the central part of the NP.…”
Section: Discussionmentioning
confidence: 99%
“…More likely, local people are aware of both positive and negative implications of tourism and draw their conclusions based on the relative weightings they attach to the benefits and the costs (Andriotis & Vaughan, 2003). The view of Andriotis and Vaughan (2003) agrees with Butler's (1980) view which states that community attitudes towards tourism invariably simultaneously reveal both positive and negative aspects. Sharpley and Sharpley (1997) also conclude that local people's attitudes towards tourism can be both positive and negative.…”
Section: Tourism Impact and Local Communities' Views Of Changes Causementioning
confidence: 93%
“…Through the review of data collection methods in past tourism studies (e.g. Andereck & Vogt, 2000;Andriotis & Vaughan, 2003;Bramwell, 2003;Burns & Sancho, 2003;De Bres & Davis, 2001;Getz & Nilsson, 2004;Kuvan & Akan, 2005), some crucial issues emerged (Jimura, 2009a). As Pearce, Moscardo, and Ross (1996) argue, most studies ask questionnaire respondents to rate in some way a list of tourism impacts and very few studies develop this list from respondents, or give their respondents an opportunity to add to or comment on these lists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by several authors, the understanding of host communities' preferences toward tourism is fundamental for its development and sustainability, especially in the long run (e.g. Allen et al 1988;Lankford and Howard 1994;Ap and Crapton 1998;Gursoy et al 2002;Andriotis and Vaughan 2003).…”
Section: Introductionmentioning
confidence: 99%